Environmentally Friendly Consumption Behavior Viewed from Economic Learning, Environmental Knowledge, and Peer Influence - Mita Pramudita Nafisatunnikmah; Indri Murniawaty (UM Purwokerto Press, 2024)
The purpose of this study was to determine the effect of economic learning, environmental knowledge and peer influence on green consumption behavior in SMA Negeri 4 Semarang students. The type of research used is quantitative. The population in this study were all students of class XI SMA Negeri 4 Semarang as many as 396 students. The number of samples used was 199 students obtained using the slovin formula. The sampling technique used is proportional random sampling. This study uses a questionnaire to collect data. The data analysis technique used is descriptive statistic analysis and multiple linear regression analysis. The results of the study show that economic learning and environmental knowledge has a positive and significant effect on green consumption behavior. Peer influence has no effect on green consumption behavior. The suggestion this study is that teachers can internalize insights about the environment in learning, especially in economics learning, then students are expected to be able to increase their ecological knowledge so that they are able to preserve the environment and be rational in choosing peer environment so that they are wiser in their consumption behaviour.